Pengaruh Intensitas Penggunaan Gadget Terhadap Minat Belajar Siswa MI/SD - Filly Fitriani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Abstract : The Influence of Intensity Use of Gadgets on Learning Interests of Mi/SD Students. The purpose of this study was to determine the effect of the intensity of using gadgets on students' learning interest. This research is a research using a qualitative approach with descriptive methods on the intensity of gadget use as the independent variable and interest in learning as the dependent variable. The research data was obtained using literature study techniques. From various sources, there are negative and positive impacts that can be taken from using gadgets. From the analysis of the sources of using gadgets it is very influential for students' learning interest, if children make good use of gadgets to find information about lessons, students' interest in learning will increase because gadget features help students to learn, while the intensity of excessive use of gadgets will make students not interested. in learning because of addiction to gadgets.